Professional identity formation in sports teachers: a multifactorial analysis - Madina Ishkibayeva; Zhazira Abdykhalykova; Nursulu Makhambetova; Bota Kabylzhanova (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The modern sports education system is undergoing a significant transformation due to global changes in sports and new requirements for the training of young athletes.